Effects of Carbonization Conditions on Structure and Gas Adsorption of Carbon Membranes Derived from Polyvinyl Chloride. Issue 3 (17th January 2020) - Xu, Beiyu; Zhao, Xinpeng; Chen, Hao; Su, Shengpei; Yu, Haibin
Abstract: Carbon membranes were fabricated through the pre‐oxidation and pyrolysis of polyvinyl chloride (PVC). Their chemical composition and structure morphology were characterized using FTIR, SEM and XRD; their CO2 and N2 adsorption isotherms were measured at 25 °C. The experimental results showed that heating rate and holding time have great influences on the pore structure during the pre‐oxidation process as well as the carbonization process. The pore structure of the carbon membrane is also influenced by carbonization temperature. The carbon membrane obtained at 700 °C has the largest CO2 adsorption capacity of 1.45 mmol/g at 101 kPa. The carbon membrane prepared at heating rate of 3 °C/min and holding time of 0.5 h at 800 °C displayed an excellent adsorption selectivity of CO2 over N2 evidenced by the fact that its CO2 adsorption capacity could reach 1.1 mmol/g and while it does not significantly adsorb N2 . Abstract : Carbon membranes can be fabricated through the pre‐oxidation and carbonization of polyvinyl chloride (PVC). The pore structure of the carbon membranes can be adjusted by changing the carbonization conditions. The PVC carbon membrane displayed an excellent adsorption selectivity of CO2 over N2 evidenced by the fact that its CO2 adsorption capacity could reach 1.1 mmol/g and while it does not significantly adsorb N2 .